A microsite for Zorrilla’s bicentenary. The Real Academia Española’s Archive and the (no longer) new technologies - de Quintana, Covadonga (Revista General de Información y Documentación, 2018)
Nowadays, where the professional archivists have to develop archival marketing techniques to achieve the outreach and enhancement of the archival fonds they work with, the department of Archives and Records Administration of the Real Academia Española decided to build a microsite to commemorate José Zorrilla’s birth bicentenary. In order to display the archival material related to the poet, the microsite was conceived as an on-line source of universal access, not only as a dissemination tool but also as a claim for attending to the primary sources when attempting a research; therefore, it had a slight scientific orientation. The work, simultaneously performed in two levels, informative and technical, has allowed the Real Academia Española Archives’ transition to the Web 3.0.